The Influence Of Work Discipline, Work-Life Balance, Employee Engagement On Employee Performance at PT Globalindo Intimates Klaten - Vanya Divka Putri Maharani; Agus Suyatno; Khabib Alia Akhmad (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the impact of work discipline, work-life balance, and employee engagement on employee performance at PT Globalindo Intimates Klaten. The population for this research consisted of approximately 3,000 employees, with a sample of 97 respondents selected using purposive sampling. This sampling method was employed to target employees who met specific criteria relevant to the research objectives. The data for the study were collected through a questionnaire that utilized a Likert scale, and the analysis was conducted using SPSS software. The analytical process included validity and reliability tests, classical assumption tests, and hypothesis testing. The results of the study indicated that work discipline, work-life balance, and employee engagement had a positive and significant effect on employee performance, both independently and in combination. Specifically, work discipline plays a key role in ensuring that employees adhere to organizational rules and regulations, which contributes to improved performance. Work-life balance helps employees manage their personal and professional lives, reducing stress and improving overall job satisfaction, which in turn enhances performance. Employee engagement, which refers to the level of enthusiasm and commitment employees have toward their work, was found to significantly influence their performance as well. The study suggests that organizations should focus on fostering a strong work ethic, providing support for work-life balance, and increasing employee engagement in order to improve overall performance. The findings emphasize that when employees are disciplined, maintain a healthy work-life balance, and are engaged with their work, their productivity increases, leading to improved outcomes for the organization. This research highlights the importance of these factors in creating a motivated and high-performing workforce, and the results can be used to inform human resource strategies in other organizations aiming to improve employee performance and achieve organizational success.